Ag-Coated Cu/Polylactic Acid Composite Filament for Lithium and Sodium-Ion Battery Current Collector Three-Dimensional Printing via Thermoplastic Material Extrusion - Maurel, Alexis; Kim, Hyeonseok; Russo, Roberto; Grugeon, Sylvie; Armand, Michel; Panier, Stephane; Dupont, Loic (Frontiers in Energy Research, 2021)
This article focuses on the development of polylactic acid– (PLA-) based thermoplastic composite filament for its use, once 3D printed via thermoplastic material extrusion (TME), as current collector at the negative electrode side of a lithium-ion battery or sodium-ion battery. High electronic conductivity is achieved through the introduction of Ag-coated Cu charges, while appropriate mechanical performance to allow printability was maintained through the incorporation of poly(ethylene glycol) dimethyl ether average Mn ∼ 500 (PEGDME500) as a plasticizer into the PLA polymer matrix. Herein, thermal, electrical, morphological, electrochemical, and printability characteristics are discussed thoroughly. While Ag-Li alloy formation is reported at 0.1V upon cycling, its use with active materials such as Li4Ti5O12 (LTO) or Li2-terephthalate (Li2TP) operating at a plateau at higher potential is demonstrated. Furthermore, its ability to be used with negative electrode active material of sodium-ion battery technology in a wide potential window is demonstrated.